2022
DOI: 10.3389/fcvm.2022.907664
|View full text |Cite
|
Sign up to set email alerts
|

Non-pharmacological Management in Palliative Care for Patients With Advanced COPD

Abstract: Chronic obstructive pulmonary disease (COPD) is a disabling condition associated with progressive airflow limitation and lung tissue damage; its main symptoms are breathlessness, fatigue, cough, and sputum production. In the advanced stage of the disease, these symptoms may severely impact on a person's physical and psychological functioning, with some also developing chronic respiratory failure, associated with blood gas abnormalities. Non-pharmacological interventions can improve quality of life and function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 120 publications
0
8
0
Order By: Relevance
“…In this complex clinical scenario, non-invasive ventilation (NIV) can be implemented to provide respiratory support without the need for invasive interventions including intubation and invasive mechanical ventilation [ 6 ]. Therefore, NIV can be employed for specialized palliative care for facing respiratory symptoms and optimizing the patient’s quality of life [ 7 , 8 ]. This therapeutic approach can foster improved sleep, alleviate anxiety, and enhance comfort, empowering patients to engage more fully in meaningful activities and interactions with their loved ones [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this complex clinical scenario, non-invasive ventilation (NIV) can be implemented to provide respiratory support without the need for invasive interventions including intubation and invasive mechanical ventilation [ 6 ]. Therefore, NIV can be employed for specialized palliative care for facing respiratory symptoms and optimizing the patient’s quality of life [ 7 , 8 ]. This therapeutic approach can foster improved sleep, alleviate anxiety, and enhance comfort, empowering patients to engage more fully in meaningful activities and interactions with their loved ones [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…While non-pharmacological techniques are low risk and low cost, they are underutilised 4 and may not be effective for all patients with breathlessness. 5 The need for novel, evidence-based, non-pharmacological approaches to managing breathlessness is urgent.…”
mentioning
confidence: 99%
“…Individualized approaches to managing breathlessness may include pharmacological agents and non‐pharmacological techniques, such as the use of hand‐held fans, breathing exercises or postures to ease breathlessness. While non‐pharmacological techniques are low risk and low cost, they are underutilised 4 and may not be effective for all patients with breathlessness 5 . The need for novel, evidence‐based, non‐pharmacological approaches to managing breathlessness is urgent.…”
mentioning
confidence: 99%
“…The initiation of palliative respiratory care should be based on the severity of patient's symptoms and unmet needs [31]. In the late stage of COPD, respiratory symptoms (shortness of breath, cough, fatigue) heavily influence the physical and psychological functioning of a person, accelerate the progression of chronic respiratory failure and reduce the quality of life, that results in disability [27].…”
mentioning
confidence: 99%
“…Evaluating an interdisciplinary approach to the management of patients with progressive COPD at the palliative stage, A. Pyszora et al [27] have shown positive effects of such methods of physical therapy as pulmonary rehabilitation, physical activity, neuromuscular electrical stimulation and methods for cleaning the respiratory tract.…”
mentioning
confidence: 99%